Understanding strategic decisions of digital agricultural platform companies: Six case studies of Sub-Saharan African platforms - Matthias von Bismarck-Osten (University of Bonn, Center for Development Research (ZEF), 2021)
Over the last seven years, digital agricultural platforms offering a broad range of products and digital services to smallholder farmers have gained a dominant position on the African market. This paper examines the predictions of platform theory using case study evidence from six companies in SubSaharan Africa. The platform companies profiled in this paper are DigiFarm, FarmCrowdy, AgroMall, Twiga Foods, Tulaa and AgroCenta. While in theory platforms limit themselves to establishing linkages between user groups, the platform companies profiled in this paper have built vertical structures of control and integration into their business model, albeit to a varying degree. These include the maintenance of a field force that advises and accompanies the farmers, logistics and, above all, the direct sale of the farmers' produce on the platform company's own account. Thus, very different platform models are all subsumed under the term ' digital agricultural platforms '. With recourse to economic theory on platforms, the paper proposes categories with greater discriminatory power. In addition, it describes how platform companies make key strategic decisions as set out in economic theory. Finally, owing to varying contexts, the paper concludes that there is no silver bullet for the establishment of a digital agricultural platforms.
Keywords: D21; Q12; Q13; Q19; O32; O33; 330; Sub Saharan Africa; rural development; digital agricultural platforms; digital services for agriculture (D4Ag); agricultural value chain management; theory on platforms